Analisis Nilai Perjuangan Tokoh Utama Pada Film Battle Of Surabaya Disutradarai Oleh Aryanto Yuniawan - Dicky Wahyu Andika; Albertus Purwaka; Patrisia Cuesdeyeni; Alifiah Nurachmana; Lazarus linarto (Universitas Palangka Raya, 2023)
The purpose of this study is to describe the value of struggle figure main in the movie Battle of Surabaya directed by Aryanto Yuniawan. The problem explored in this research is the value of the struggle with the form of the value of the struggle which includes (1) the value of struggle willing sacrifice (2) value struggle unity (3) value struggle price-appreciate (4) value struggle abstinence give up (5) value struggle work same. This study used descriptive qualitative method. The subject of this research is an animated film entitled Battle of Surabaya directed by Aryanto Yuniawan. Data collection procedures in this study used non-participant observation techniques, documentation techniques, viewing techniques, and note-taking techniques. The results of this study indicate that the value of struggle figure main role in the film Battle of Surabaya directed by Aryanto Yuniawan with the form of values shows (a) the value of never giving up struggle in the film there are 5 forms of the value of never giving up struggle. (b) the value of struggle willing sacrifice in the film shows 3 forms of the value of struggle willing sacrifice. (c) the value of struggle Unity in the film shows 2 forms of the value of struggle union. (d) value of struggle price-appreciation in the film shows 3 forms of value struggle price-appreciate. (e) value struggle work same in the film shows 2 forms value struggle work same.